Stronger maternal social bonds and higher rank are associated with accelerated infant maturation in Kinda baboons. (July 2022) - Schneider-Crease, India A.; Weyher, Anna H.; Mubemba, Benjamin; Kamilar, Jason M.; Petersdorf, Megan; Chiou, Kenneth L.
Abstract : Social relationships are critical components of health and fitness for humans and other animals. For female-philopatric species, affiliative relationships among females (kin and nonkin alike) can influence components of fitness that include individual survival, interbirth interval and offspring survival. Affiliative relationships with males have attracted somewhat less attention, with most studies focusing on female–male relationships as adaptations for infanticide avoidance. Here, we use 8 years of behavioural data on Kinda baboons, Papio kindae, to assess whether maternal social relationships—both among females and between females and males—affect infant survival, interbirth interval and the pace of infant development. Kinda baboons are an ideal system for these analyses because males and females form strong relationships outside of the periovulatory period and in the absence of obvious infanticide threat. We calculated social metrics that reflected dominance status, total social integration and social bond strength and paired these metrics with data on offspring survival, interbirth interval (IBI) duration and infant behavioural maturation. Neither dominance rank nor sociality had a significant effect on interbirth interval or survival, but higher rank and the stronger affiliative relationships between a female and her top female and top male social partners predicted more rapid infant behavioural maturation. These results suggest that maternal dominance and sociality may confer advantages related to infant development and independence that ultimately may permit females to more quickly invest in subsequent offspring and point to advantages of relationships with males outside of lowering infanticide threat. Highlights: Kinda baboon female–male bonds persist outside of fertility or infanticide threat. Social bonds did not affect interbirth interval or infant survival and growth. Dominance and affiliative bonds predicted more rapid infant development. Top-partner bonds were the strongest predictors of infant development. Strong maternal bonds with females and males enhanced infant development.